2013
DOI: 10.1002/chem.201202948
|View full text |Cite
|
Sign up to set email alerts
|

Popcorn‐Shaped Magnetic Core–Plasmonic Shell Multifunctional Nanoparticles for the Targeted Magnetic Separation and Enrichment, Label‐Free SERS Imaging, and Photothermal Destruction of Multidrug‐Resistant Bacteria

Abstract: Over the last few years, one of the most important and complex problems facing our society is treating infectious diseases caused by multidrug-resistant bacteria (MDRB), by using current market-existing antibiotics. Driven by this need, we report for the first time the development of the multifunctional popcorn-shaped iron magnetic core-gold plasmonic shell nanotechnology-driven approach for targeted magnetic separation and enrichment, label-free surface-enhanced Raman spectroscopy (SERS) detection, and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 94 publications
0
98
0
5
Order By: Relevance
“…Fan et al described the generation of popcorn shaped magnetic nanoparticles which consisted of an iron core and a gold shell. [116] The nanostructures were further labelled with an antibody with affinity for Salmonella DT104. [116] In the study the nanoparticles were found to bind to the Salmonella cells with high affinity and, because of their magnetic properties, cells could be extracted from the bulk solution.…”
Section: Sers As a Methods For Disease Treatmentmentioning
confidence: 99%
“…Fan et al described the generation of popcorn shaped magnetic nanoparticles which consisted of an iron core and a gold shell. [116] The nanostructures were further labelled with an antibody with affinity for Salmonella DT104. [116] In the study the nanoparticles were found to bind to the Salmonella cells with high affinity and, because of their magnetic properties, cells could be extracted from the bulk solution.…”
Section: Sers As a Methods For Disease Treatmentmentioning
confidence: 99%
“…С и н т е з Г Н Ч Ag/FeСo/Ag. ГНЧ Ag/FeСo/Ag типа Я/О/О были синтезированы по способу, описан-ному в [5,7,8]. Были подготовлены два типа растворов.…”
Section: экспериментальные методикиunclassified
“…Значительное внимание исследователей в последние годы привлекают магнитные плазмонно-резонансные (ПР) гибридные наноразмерные частицы (ГНЧ), потому что весьма перспективны для широкого круга примене-ний, в том числе в биомедицине для адресной доставки лекарств, терапии рака, усиления контрастности томо-графических снимков [1][2][3][4], магнитной сепарации, обра-ботки изображений [5]. Адресная доставка с помощью ПР ГНЧ основана на том, что их можно подвергать биоконъюгации, т. е. прикреплять к ним биомолекулы (ДНК/РНК, белки, олигосахариды и др.)…”
Section: Introductionunclassified
See 2 more Smart Citations